Who are the active investors? Evidence from Venture Capital - Laura Bottazzi; Marco Da Rin; Thomas Hellmann (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
are the active investors? Evidence from Venture Capital Abstract: This paper examines the determinants and consequences of investor activism in venture capital. Using a hand-collected sample of European venture capital deals, it shows the importance of human capital. Venture capital firms with partners that have prior business experience are more active recruiting managers and directors, helping with fundraising, and interacting more frequently with their portfolio companies. Independent venture capital firms are also more active than 'captive' (bank-, corporate-, or government-owned) firms. After controlling for endogeneity, investor activism is shown to be positively related to the success of portfolio companies.
Keywords: 330